Menopausal shift on women’s health and microbial niches - Maria R. Nieto; Maria J. Rus; Victoria Areal-Quecuty; Daniel M. Lubián-López; Aurea Simon-Soro (npj Women's Health)
Abstract Menopause marks a key milestone in women’s aging, triggering hormonal, histological, and microbiome changes. This review explores how hormonal shifts during menopause alter the microbiome’s composition, affecting oral, intestinal, and urogenital communities, potentially leading to disease. The microbial metabolism of sex hormones highlights the bidirectional relationship between hormones and the microbiome. Understanding this interplay is crucial for developing personalized interventions to restore microbial balance and improve women’s health during menopause.